Community Pharmacy Services: Beyond Dispensing Medications (Journal of Namibian Studies : History Politics Culture, 2022)
Community pharmacies have undergone a transformation from traditional medication dispensaries to multifaceted healthcare centers. This evolution has seen pharmacists assume expanded roles in delivering comprehensive services beyond mere drug distribution. This article explores the diverse array of services offered by community pharmacies, including Medication Therapy Management (MTM), immunizations, chronic disease management, smoking cessation programs, health screenings, wellness initiatives, collaborative care, and technology integration. Through these services, pharmacists play a crucial role in optimizing medication regimens, promoting preventive care, and improving patient outcomes.